Mental Models of School for Preschool Children - Ki̇ldan, A. Oguzhan; Kurnaz, Mehmet Altan; Ahi̇, Berat (Eurasian Society of Educational Research, 2013)
The aim of this study was to determine mental models of 334 pre-school children concerning school. Children in the city center of Kastamonu in the Western Black Sea region of Turkey were included. Content analysis was conducted on pictures drawn by the children, and the models were split into two groups, scientific and nonscientific. The scientific group was split into three types; the nonscientific group, into four. About 40% of the children had a scientificbased school perception, while 60% were nonscientific. No significant difference was found between the mental models of females and males. Few studies have investigated mental models, so this study fills a gap, but further studies would aid the understanding of the relevant pedagogic architecture.
Keywords: mental model; pre-school child; drawing picture; school; Eğitim Üzerine Çalışmalar; Studies on Education; 4. Education